2021
DOI: 10.20858/sjsutst.2021.110.9
|View full text |Cite
|
Sign up to set email alerts
|

Teeth deformation of non-circular gears

Abstract: In practice, gear units whose transmission number is not constant during one revolution are used. Such gears include the proposed elliptical transmission. Its application can be (missing a word?) and the automotive industry. The gears set consists of a pair of identical elliptical gears. The transmission ratio of the designed elliptical gear is not constant. The basic kinematic characteristics of this transmission are described in this work. The deformation in contact point of non - circular gears is determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…In Ref. 65 the deformation of the teeth of a non-circular elliptical gear was analysed. It was found that the actual load on the teeth is variable and the deformation of cooperating pairs of teeth is also variable.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 65 the deformation of the teeth of a non-circular elliptical gear was analysed. It was found that the actual load on the teeth is variable and the deformation of cooperating pairs of teeth is also variable.…”
Section: Introductionmentioning
confidence: 99%
“…Digital mapping is understood as a recording of parameters of operational conditions of ecological continuous transport systems. Specifically, these are conditions such as a normal operation, identification of criteria signaling emergence of undesirable operating states [17], etc. In digital mapping, specific indicators and parameters need to be focused on.…”
Section: Digital Transformation In Intralogisticsmentioning
confidence: 99%
“…Eliptik dişlilerin de yapısal analizleri bilgisayar destekli paket programlar aracılığıyla gerçekleştirilebilmektedir. Dairesel olmayan dişlilerin temas noktalarındaki deformasyonunun belirlenmesine yönelik, sonlu elemanlar yönteminin kullanıldığı ve sonuçlarının, düz dişlilerin sonuçları ile kıyaslandığı tespit edilmiştir [55]. Dairesel olmayan dişlilerin düz dişliler ile kıyaslanma nedeni, literatürde düz dişliler ile ilgili verilerin detaylı bir şekilde bulunması ve dairesel olmayan dişlilerin, düz dişliler yerine kullanılıp kullanılmayacağı hakkında bilgi sahibi olunmak istenmesidir.…”
Section: Bilgisayar Destekli Mühendislik Ile Analizunclassified
“…Dairesel olmayan dişlilerin düz dişliler ile kıyaslanma nedeni, literatürde düz dişliler ile ilgili verilerin detaylı bir şekilde bulunması ve dairesel olmayan dişlilerin, düz dişliler yerine kullanılıp kullanılmayacağı hakkında bilgi sahibi olunmak istenmesidir. Yapılan bir diğer çalışmada, dairesel olmayan dişlilerin değişken çevrim oranından dolayı dişli 3 bölgeye ayrılmış, dairesel olmayan dişlinin deformasyonunun, her bir dişte teğetsel kuvvetin değişmesi ve kavrama hattının uzunluklarının, dolayısıyla kavrama süresinin farklığından kaynaklı olarak, standart düz dişliye göre farklı olduğunu görülmüştür [55]. Bölüm elipsini sonlu mikro dilimlere bölünerek dinamik bir model oluşturulan çalışmada, modelleme doğruluğunu artırmak için zamana bağlı sonlu elemanlar yöntemini esas almışlardır [56].…”
Section: Bilgisayar Destekli Mühendislik Ile Analizunclassified